Effect of Skin Melinjo Extract (Gnetum Gnemon) On Expression URAT1 and GLUT9 Genes In Hyperuricemia - Nurul Amalia Sofyan; Syafruddin Ilyas; Yetty Machrina (International Journal of Ecophysiology, 2023)
Hyperuricemia is defined as a metabolic syndrome disease with markers characteristic of uric acid production that exceed normal limits. Normal uric acid levels range from 3.4-7.0 mg/dl in adult men and 2.4 -6.0 mg/dl in adult women. So if uric acid levels exceed the normal limit, it will cause uric acid can not be fully metabolized and cause hyperuricemia. About 70% of uric acid is excreted through the kidneys. The kidneys are therefore organs that have an important role in maintaining uric acid levels and uric acid homeostasis in general, through complex molecular mechanisms. Reabsorption of uric acid that occurs in the kidneys by URAT1 and GLUT9 has an important role in uric acid levels in the human body, where uric acid is reabsorbed by the kidneys will then be flowed back into the blood so that it affects the levels of uric acid in the human body. Preliminary data showed that ethanol extract of melinjo skin contains 3 main Flavonoid compounds that have a higher Binding affinity value compared to allopurinol, so it has a higher effect in overcoming uric acid levels.